2014
DOI: 10.1128/aem.03293-13
|View full text |Cite
|
Sign up to set email alerts
|

High Salinity Alters the Germination Behavior of Bacillus subtilis Spores with Nutrient and Nonnutrient Germinants

Abstract: The effect of high NaCl concentrations on nutrient and nonnutrient germination of Bacillus subtilis spores was systematically investigated. Under all conditions, increasing NaCl concentrations caused increasing, albeit reversible, inhibition of germination. High salinity delayed and increased the heterogeneity of germination initiation, slowed the germination kinetics of individual spores and the whole spore population, and decreased the overall germination efficiency, as observed by a variety of different ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 46 publications
(78 reference statements)
5
61
0
Order By: Relevance
“…Phasecontrast microscopy further revealed that at 0.6 to 2.4 M NaCl, while the vast majority of decoated spores were able to exit the phase-bright (i.e., dormant) state, many turned only phase gray instead of phase dark (data not shown). As reported previously (23), the latter finding might indicate the successful initiation of germination but inhibition of the completion of germination. In the presence of 3.6 M NaCl, most decoated spores remained phase bright, although some phase-gray spores were also present.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Phasecontrast microscopy further revealed that at 0.6 to 2.4 M NaCl, while the vast majority of decoated spores were able to exit the phase-bright (i.e., dormant) state, many turned only phase gray instead of phase dark (data not shown). As reported previously (23), the latter finding might indicate the successful initiation of germination but inhibition of the completion of germination. In the presence of 3.6 M NaCl, most decoated spores remained phase bright, although some phase-gray spores were also present.…”
Section: Resultssupporting
confidence: 57%
“…6A and B). As for nutrient-dependent germination, the extent of NaCl inhibition increased with increasing NaCl concentrations (23). Importantly, even at up to 3.6 M NaCl, noticeable germination could be induced by 150 MPa and significant amounts of DPA (ca.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations